(untitled) (American International Journal of Agricultural Studies, 2021)
Due to the high cost of tomato seeds, it is important to fully exploit the seeds for economic gains. This has necessitated the use of vine cutting technology in tomato production from vegetative parts. However, the vine acclimatization substrates type plays important role in the survival of the cut vines. Hence, this study investigates three different substrate types (cocopeat, water and loamy soil) for their suitability for vines cutting. Seeds of three tomato genotypes were raised in hydroponics system containing dissolved cocopeat. At one month after planting, vines were cut from the plants into the three substrates in a Completely Randomized Design with three replicates. Data were collected on vine survival, days to new shoot formation, number of fruits per plant and the average fruit weight at harvest. Data collected were analyzed using ANOVA and differences in the treatment means were separated using the Least Significant Differences at 5 % level of significance. Results obtained showed that the percentage vine survival across the substrates was insignificant with a success rate of up to 77 % in the loamy soil. However, new shoot formation was fastest in the cocopeat substrate (12.56±0.53), while San marzano had the heaviest fruit size (20.73±1.33).